2021
DOI: 10.1002/tqem.21784
|View full text |Cite
|
Sign up to set email alerts
|

Future perspectives and mitigation strategies towards groundwater arsenic contamination in West Bengal, India

Abstract: Arsenic is a toxic carcinogen mostly found in subsurface environments. It is released into groundwater mostly via natural geological and hydrological processes. Consumption of such contaminated water leads to serious health crises for mankind. Developing countries in South Asia, particularly the rural regions, have been severely affected by this environmental phenomenon. In India, government authorities have implemented several remedial measures to provide safe drinking water to the rural habitations, ranging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(12 citation statements)
references
References 400 publications
(393 reference statements)
0
8
0
Order By: Relevance
“…Furthermore, this kinetic model can also be extended to comprehend the dynamic mechanisms of physiochemical and ecological processes occurring in terrestrial (Jafarpour & Khatami, 2021) and riverine ecosystems (Koley, 2021) via appropriate model calibrations. Based on calibrated models and tunable parameters, relevant policies of environmental management and technologies of ecological engineering could be developed to promote sustainable development of the regional economy, society and environment.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, this kinetic model can also be extended to comprehend the dynamic mechanisms of physiochemical and ecological processes occurring in terrestrial (Jafarpour & Khatami, 2021) and riverine ecosystems (Koley, 2021) via appropriate model calibrations. Based on calibrated models and tunable parameters, relevant policies of environmental management and technologies of ecological engineering could be developed to promote sustainable development of the regional economy, society and environment.…”
Section: Resultsmentioning
confidence: 99%
“…For the strategy of mixing As WTRs with organic waste, the system boundary does not include the organic residues (e.g., cow dung). The fraction of As converted to volatilized species (90%) and the aqueous phase (10%) during disposal was estimated from the available scientific literature. Finally, for open disposal, this strategy was assumed to occur via dumping As WTRs directly into surface waters, consistent with the documented literature. , This system boundary includes the As flows arising from As leaching from the WTRs, which is estimated to be 90% to the aqueous phase and 10% to soils (sediment). , …”
Section: Life Cycle Assessmentmentioning
confidence: 99%
“…These strategies are locally manageable and less infrastructure-intensive than landfilling but have less waste control. In general, ODPs can be divided into three groups (Figure ): ,, (i) stabilization in building materials, (ii) mixture with organic waste, and (iii) open disposal without adequate site preparation. Stabilization in building materials is a less-controlled disposal strategy that typically involves incorporating the As WTRs in bricks for subsequent use in local construction. However, incorporating As WTRs in bricks decreases brick compression strength and structural integrity, which is consistent with our field observations in South Asia of highly eroded bricks produced with As WTRs that crumble and deteriorate rapidly .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Drinking water treatment facilities generate vast quantities of residuals that are filled with contaminants. , These water treatment residuals (WTRs) are commonly discharged in landfills in regions with sufficient space and resources. , However, in As-affected areas in rural South Asia, management of As-bearing WTRs is poor, leading to the open disposal of As-bearing WTRs to ponds, rivers, and soils without any site preparation. , A problem in the management of As-bearing WTRs is inadequate testing procedures that are not representative of actual conditions in the disposal sites, thus leading to over- or underprediction of As remobilization . Common leach tests, such as the toxicity characteristic leaching procedure (TCLP), have been shown to underpredict As mobilization from WTRs in landfills , since the tests do not account for microbial activities that change over long periods and redox fluctuations. , A recent study indicated that open disposal strategies especially pose the highest potential risk to the environment and human health …”
Section: Introductionmentioning
confidence: 99%